Handling Words Duplication and Memory Management for Digital Quran Based on Hexadecimal Representation and Sparse Matrix - Ashraf Al-Omoush; Norita Md Norwawi; Ahmad Akmalludin Mazlan (Science Publishing Corporation Inc., 2024)
Volume:7 No:4.15